Perancangan Grafis Lingkungan Kampung Sepatu Kota Mojokerto - Airlangga, Eka Mas Tommy; Setiawan, Bayu; Nisa, Diana Aqidatun (Peneliti.net, 2024)
Environmental Graphics Design is a design approach that integrates graphic elements into the environment to provide information that helps visitors determine locations and enhance their experience at the visited site. The design of Environmental Graphics Design in public places is crucial, especially in Kampung Shoes, Mojokerto City, located in Miji Village, Kraggan District, Mojokerto City.The research method applied is qualitative and quantitative, with Kampung Shoes, Mojokerto City, selected as a case study for the design. Data was collected through observation, interviews, literature studies, and distributing questionnaires to predetermined target audiences. The data analysis process involves identifying visitors' information needs, evaluating the existing environmental graphic design conditions at the location, and identifying problems related to environmental graphics in Kampung Shoes, Mojokerto City.After analysis, the data sites are used as the basis for this design and the keyword taken is